FranchiseGlobal.com: Digital Media Strategy in the Development of Franchise Industry and Business Opportunities in Indonesia - Ningsih, Susilowati; Hamdi, Edi; Indradewa, Rhian; Abadi, Ferryal (Journal La Bisecoman, 2024)
The franchise and business opportunity industry in Indonesia has experienced significant growth, particularly with the emergence of digital media platforms that facilitate connections between franchisors and prospective franchisees. FranchiseGlobal.com stands as a key online media platform playing a pivotal role in this industry. This study aims to analyze the digital media strategies employed by FranchiseGlobal.com in advancing the franchise and business opportunity sector in Indonesia. The research adopts a descriptive analysis with a case study approach, focusing on FranchiseGlobal.com's business model, digital marketing strategies, and its role in supporting franchise expansion. The findings reveal that FranchiseGlobal.com has effectively utilized digital media to enhance franchise visibility through services such as advertising, content distribution, and online business matching. The study concludes that an effective digital strategy can significantly contribute to the growth of the franchise industry in Indonesia, particularly by leveraging online platforms that reach a broad and targeted audience.